2010
DOI: 10.1017/s003118201000079x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two fatty acid binding proteins fromFasciola gigantica

Abstract: Fatty acid binding proteins are considered to be promising vaccine candidates against trematodiasis. In order to provide additional information about their function in Fasciola gigantica we performed a comparative analysis of FgFABP1 and FgFABP3, two isoforms with quite different isoelectric points of 4.9 and 9.9 and 67% sequence identity. Both are expressed in the juvenile and adult parasite but differ in their tissue-specific distribution. In addition, the sequence of FABP3 is identical in F. hepatica and F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Estimates of infection rates are as high as 80-100% in some countries [1-5]. Despite the importance to differentiate between the infection by fasciolid species, due to their distinct epidemiological, pathological, and control characteristics, there is, unfortunately, neither a direct coprological (excretion-related) nor an indirect immunological test is available for their diagnosis [6,7]. The quantification of the different sizes and shapes of F. hepatica and F. gigantica from bovines has been achieved for the first time in natural allopatric populations [8].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of infection rates are as high as 80-100% in some countries [1-5]. Despite the importance to differentiate between the infection by fasciolid species, due to their distinct epidemiological, pathological, and control characteristics, there is, unfortunately, neither a direct coprological (excretion-related) nor an indirect immunological test is available for their diagnosis [6,7]. The quantification of the different sizes and shapes of F. hepatica and F. gigantica from bovines has been achieved for the first time in natural allopatric populations [8].…”
Section: Discussionmentioning
confidence: 99%
“…Appearance of the protein in eggs in the womb demonstrated that energy from fatty acid oxidation may be very important for growth, development and even survival after the eggs are discharged to the outer environment [ 21 ]. FABPs transport fatty acids from the host, while parasitic helminths cannot synthesize some fatty acids themselves [ 28 ], making FABPs necessary throughout the B . schroederi body.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of OvROPN1L in adult (6-week-old) parasites was analyzed in paraffin-embedded tissue as previously described (Chunchob et al, 2010). Mouse anti-rOvROPN1L antiserum was used at dilution 1:200, mouse preimmune serum at the same dilution was used as negative control.…”
Section: Immunohistochemical Detection Of Ovropn1l In Adult Parasitesmentioning
confidence: 99%